Tumor characteristics and outcome of uterine carcinosarcoma in women aged ≥80 years. (June 2019) - Matsuo, Koji; Ross, Malcolm S.; Yunokawa, Mayu; Johnson, Marian S.; Machida, Hiroko; Omatsu, Kohei; Klobocista, Merieme M.; Im, Dwight D.; Satoh, Shinya; Baba, Tsukasa; Ikeda, Yuji; Bush, Stephen H.; et al.
Abstract: Objective: To examine clinico-pathological characteristics and outcomes of uterine carcinosarcoma (UCS) in women aged ≥80 years. Methods: This is a secondary analysis of a previous multicenter retrospective study examining 906 women with stage I–IV UCS who underwent primary hysterectomy. Patient demographics, treatment types, tumor characteristics, and survival were examined across aged ≥80 ( n  = 82 [9.1%]), aged 60–79, ( n  = 526 [58.1%]), and aged <60 ( n  = 298 [32.9%]). Results: Women in the aged ≥80 group were more likely to be Caucasian, undergo simple hysterectomy without lymphadenectomy, and receive no postoperative therapy (all, P  < 0.05). Tumors in the aged ≥80 group were more likely to have high-grade carcinoma, heterologous sarcoma, and sarcoma dominance but less likely to have lympho-vascular space invasion (all, P  < 0.05). Lymphadenectomy did not improve survival in the aged ≥80 group ( P  > 0.05), whereas lymphadenectomy was protective for survival in the younger groups (both, P  < 0.05). Postoperative chemotherapy was associated with improved progression-free survival (PFS) in the aged ≥80 group (hazard ratio [HR] 0.44, 95% confidence interval [CI] 0.22–0.89, P  = 0.021). With chemotherapy treatment, women in the aged ≥80 group had PFS similar to those in the aged 60–79 group (HR 0.97, 95%CI 0.51–1.83, P  = 0.92). In contrast, without chemotherapy treatment, women in the aged ≥80 group had significantly decreased PFS compared to the aged 60–79 group (HR 1.62, 95%CI 1.09–2.40, P  = 0.016). Similar associations were observed for postoperative radiotherapy. Conclusion: Nearly 10% of women with UCS are aged ≥80 that are characterized by aggressive tumor factors. Postoperative therapy but not extensive surgery may improve survival in this age group. Highlights: Women aged ≥80 account for ∼10% of uterine carcinosarcoma. Tumors of women aged ≥80 exhibit high-grade carcinoma and heterologous sarcoma. Women aged ≥80 are likely to undergo simple hysterectomy without lymphadenectomy. Women aged ≥80 are less likely to receive postop chemotherapy/radiotherapy. Postop therapy but not lymphadenectomy may improve survival in women aged ≥80.